CDR 2020
DOI: 10.20517/cdr.2019.103
|View full text |Cite
|
Sign up to set email alerts
|

The power of microRNAs as diagnostic and prognostic biomarkers in liquid biopsies

Abstract: In the last decades, progresses in medical oncology have ameliorated the treatment of patients and their outcome. However, further improvements are still necessary, in particular for certain types of tumors such as pancreatic, gastric, and lung cancer as well as acute myeloid leukemia where early detection and monitoring of the disease are crucial for final patient outcome. Liquid biopsy represents a great advance in the field because it is less invasive, less time-consuming, and safer compared to classical bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 177 publications
0
31
0
Order By: Relevance
“…MiR-4732-5p played a major oncogenic role in breast cancer progression by targeting TSPAN13 [ 61 ], and potentially served as an unfavorable biomarker with miR-448, miR-486, miR-516, and miR-1911 in lung squamous cell carcinoma [ 63 ]. Up-regulated plasma based miR-4732-5p was also reported as a diagnostic and prognostic marker in pancreatic ductal adenocarcinoma patients when compared with healthy group [ 64 ]. Moreover, miR-4732-5 directly bound the 5′-untranslated regions (UTRs) of Wrap53 mRNA in breast cancer, and prohibited p53 mRNA binding [ 65 ], indicating a possible link between miR-4732-5p and the tumor suppression protein, p53 [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-4732-5p played a major oncogenic role in breast cancer progression by targeting TSPAN13 [ 61 ], and potentially served as an unfavorable biomarker with miR-448, miR-486, miR-516, and miR-1911 in lung squamous cell carcinoma [ 63 ]. Up-regulated plasma based miR-4732-5p was also reported as a diagnostic and prognostic marker in pancreatic ductal adenocarcinoma patients when compared with healthy group [ 64 ]. Moreover, miR-4732-5 directly bound the 5′-untranslated regions (UTRs) of Wrap53 mRNA in breast cancer, and prohibited p53 mRNA binding [ 65 ], indicating a possible link between miR-4732-5p and the tumor suppression protein, p53 [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al have analyzed panel of 365 miRNAs in prostate cancer serum and emerged miR-141, miR-200a, miR-200c, miR-375 and miR-210 molecules, which was significantly expressed in metastatic CRPC patients compared to age-matched healthy controls as well as in lymph metastasis samples [ 173 ]. In another study, Kelly et al demonstrated a normalization in miR-141 expression in prostate cancer patients who underwent a radical retropubic-prostatectomy 10 days post-operation [ 174 , 175 ]. Hao et al have found miR-141 and miR-21 twofold up regulated, while miR-10, -16, -34c and -125b down regulated in FFPE tissue compared to BPH specimens [ 176 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a translational point of view, miRs can be detected in up to 12 biological fluids including blood, urine, and saliva (in EV or EV-free) [ 69 ]. Several studies have shown the potential of miRs as biomarkers for cancer detection and/or prognosis [ 70 ]. In addition, miR inhibition, generally achieved by antisense oligonucleotides complementary to a specific miR (anti-miR oligonucleotides) can have a therapeutic value [ 71 , 72 ].…”
Section: Micrornas (Mirs)mentioning
confidence: 99%